2019
DOI: 10.32539/bsm.v3i2.88
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Aspects of Schizophrenia

Abstract: Abstract Schizophrenia is a common psychiatric disorder, which is characterized by severe distortion of reality; disturbances in thoughts, feelings and behavior; according to DSM V is a disorder form deviations fundamentals and characteristics of thought and perception, and by the innapropriate or blunted affect. The influence of genetics is believed to have a role in psychiatric disorders, especially if the disorder has occurred in young adults or adolescents. The pathophysiology of schizophrenia is clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…11 Apoptosis in prefrontal neuronal cortex cells will cause cell population decline, and definitely it will be followed by a decrease in receptors, especially serotonin receptors. 1,2 The decrease in these receptors send a negative feedback mechanism related to serotonin production in the raphe nucleus. This will cause a decrease in serotonin production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Apoptosis in prefrontal neuronal cortex cells will cause cell population decline, and definitely it will be followed by a decrease in receptors, especially serotonin receptors. 1,2 The decrease in these receptors send a negative feedback mechanism related to serotonin production in the raphe nucleus. This will cause a decrease in serotonin production.…”
Section: Resultsmentioning
confidence: 99%
“…This has implications for the development of various antidepressant drugs that work to increase serotonin levels, by inhibiting serotonin reuptake. [1][2][3] However, management with antidepressants is still believed to be not optimal, there are still various problems that have not been able to be solved only by increasing serotonin levels in the brain. Therefore, it is necessary to do further exploration to find out other possible pathophysiology of depressive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic cell death is essential pathophysiology behind the decreased secretion of the neurotransmitter dopamine. Several studies have shown a role for oxidative stress in the initiation of dopaminergic cell damage and death [6], [7], [8]. Oxidative stress is a condition in which oxidative reactions occur in cells, especially the cell membrane due to the large number of oxidants which are unstable compounds due to a lack of one electron.…”
Section: Introductionmentioning
confidence: 99%